2007
DOI: 10.1007/s00024-007-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment Using the High Resolution Eta and WRF Models to Forecast Heavy Precipitation over India

Abstract: In the present study using the Weather Research and Forecasting (WRF) and Eta models, recent heavy rainfall events that occurred (i) over parts of Maharastra during 26 to 27 July, 2005, (ii) over coastal Tamilnadu and south coastal Andhra Pradesh during 24 to 28 October, 2005, and (iii) the tropical cyclone of 30 September to 3 October, 2004/Monsoon Depression of 2 to 5 October 2004, that developed during the withdrawal phase of the southwest monsoon season of 2004 have been investigated. Also sensitivity expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 17 publications
(15 reference statements)
0
10
0
1
Order By: Relevance
“…Some possible factors that could contribute would be that local boundary formulation in MYJ may be more appropriately capturing the vertical environment in the complex terrain compared to the non-local YSU scheme which seeks to simulate vertical mixing and boundary layer evolution using averaged and grid representative fields. With regard to the BMJ CU emerging in the top configuration, there are a number of studies for the ISMR where it has emerged as performing "overall best" (Vaidya and Singh, 2000;Ratnam and Kumar, 2005;Vaidya, 2006;Rao et al, 2007;Kumar et al, 2010;Mukhopadhyay et al, 2010;Srinivas et al, 2013;Sikder and Hossain, 2016). As for the MP scheme, there are limited studies in comparison to those that have studied the CU configuration for the ISMR.…”
Section: Model Configuration and Experimental Setupmentioning
confidence: 99%
“…Some possible factors that could contribute would be that local boundary formulation in MYJ may be more appropriately capturing the vertical environment in the complex terrain compared to the non-local YSU scheme which seeks to simulate vertical mixing and boundary layer evolution using averaged and grid representative fields. With regard to the BMJ CU emerging in the top configuration, there are a number of studies for the ISMR where it has emerged as performing "overall best" (Vaidya and Singh, 2000;Ratnam and Kumar, 2005;Vaidya, 2006;Rao et al, 2007;Kumar et al, 2010;Mukhopadhyay et al, 2010;Srinivas et al, 2013;Sikder and Hossain, 2016). As for the MP scheme, there are limited studies in comparison to those that have studied the CU configuration for the ISMR.…”
Section: Model Configuration and Experimental Setupmentioning
confidence: 99%
“…Parameterization schemes beyond CP and MP were selected based on compatibility with the monsoon-driven climate [e.g., Ahasan and Khan, 2013;Kumar et al, 2012;Rao et al, 2007] and are also shown in Table 1. However, these parameterizations were not part of the sensitivity study.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%
“…In our parameterization and spatial resolution sensitivity experiments, the 6 hourly 18 3 18 resolution NCEP GFS final analyses data were used as the boundary in the WRF model [e.g., Rao et al, 2007]. These boundary data were available through the University Cooperation for Atmospheric Research-Research Data Archive (http://rda.ucar.edu/datasets/ds083.2/).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Mohanty et al [2] used MM5 model to simulate the Orissa super cyclone (1999). Again, WRF model has also been used in a number of studies for the simulation of tropical cyclones [3,4]. There are a number of comparative studies on the performance of the mesoscale models for severe weather events triggered by convection.…”
Section: Introductionmentioning
confidence: 99%